Assessment of the performance status of a wharf - Garrick Ombor, Pereowei (Array, 2018)
This paper suggests Fuzzy-logic-rule base method to assess the performance status of a wharf in order to classify it. The method proposed is predicated upon its ability to analyse processes and operations based on subjective judgement with little or no statistical data available. The study also shows that fuzzy-logic rule base is a veritable tool to qualitatively and quantitatively assess the status of a wharf offering ferry service. Using the model developed in this study, the performance status of Yenagoa wharf has been determined to be orange, having a (WPS) overall of 4.8. The status of the wharf has been in good agreement with the perception of stakeholders that the Yenagoa wharf needs restructuring to curb the frequent crisis occurring among stakeholders. The model also indicated those areas of the wharf’s operations needing attention. The study indicates that even though major components that determine the quality and profitability of the wharf’s ferry service are high in value, the overall status of the wharf may not be necessarily high. As such, the study method can be used to control the growing ill-feeling between boat operators and passengers while harmonizing all stakeholders (operators, passengers, and regulators etc) to work together to improve the status of the wharf.